Metabolomic and microbial diversity perspectives on Aspergillus oryzae culture-induced modifications in ovine feed utilization and rumen ecosystem - Xie, Jinglong; Wang, Caidie; Zhao, Yanhui; Li, Xiaoming; Ma, Guijun; Yang, Kailun (Frontiers in Veterinary Science, 2025)
IntroductionAspergillus oryzae culture (AOC) is widely used as a feed additive to enhance ruminant productivity and rumen function. However, the underlying mechanisms at the microbiome-metabolome interface remain poorly understood. This study aimed to elucidate how dietary AOC supplementation influences sheep production performance, rumen fermentation, microbial communities, and metabolomic profiles.MethodsTwelve rumen-fistulated sheep were randomly assigned to a control group (basal diet) and a trial group (basal diet + 1% AOC). The experiment lasted 30 days, during which production performance, nutrient digestibility, ruminal pH, volatile fatty acids (VFA), ammonia nitrogen, microbial diversity (16S rDNA sequencing), and metabolomic profiles (LC-MS) were systematically assessed.ResultsAOC supplementation significantly increased average daily gain (ADG) and neutral detergent fiber (NDF) digestibility by 7.00% (p < 0.05), and improved nitrogen retention. Total VFA and acetate concentrations were elevated, with a stable ruminal pH. Microbiome analysis revealed an increased relative abundance of Succiniclasticum and beneficial fiber-degrading taxa. Metabolomic profiling identified upregulation of antioxidant metabolites (e.g., ginsenoside Rg3, lipoamide) and activation of key pathways such as phenylalanine metabolism and the TCA cycle, alongside downregulation of inflammatory markers.DiscussionAOC enhances sheep productivity and rumen health by modulating fibrolytic microbiota, promoting VFA synthesis, and activating antioxidant and energy metabolism pathways. These findings provide a theoretical basis for the use of AOC as a sustainable feed additive to improve ruminant production efficiency and welfare.